2021
DOI: 10.1371/journal.pone.0260710
|View full text |Cite
|
Sign up to set email alerts
|

Maternal satisfaction with intrapartum care and associated factors among postpartum women at public hospitals of North Shoa Zone Ethiopia

Abstract: Background Maternal satisfaction is an essential indicator of the quality and the efficiency of the health care systems. At a time when efforts are being made globally to reduce maternal and neonatal mortality and morbidity, assessing maternal satisfaction is essential. There is a dearth of studies on maternal satisfaction with intrapartum care, particularly in the study area. This study aimed to assess maternal satisfaction with intrapartum care and associated factors among postpartum women at public hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This study nding is consistent with a study by [59] that found that educated women have better birth preparedness practices as compared to their counterparts and are therefore more likely to receive quality intrapartum care. Literature suggests that educated women are likely to have optimal antenatal care utilization and make informed decisions about maternal healthcare utilization [29,60,61]. Mothers who have adequate antenatal care visits receive information and sensitization about preparedness and expectations during labor [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study nding is consistent with a study by [59] that found that educated women have better birth preparedness practices as compared to their counterparts and are therefore more likely to receive quality intrapartum care. Literature suggests that educated women are likely to have optimal antenatal care utilization and make informed decisions about maternal healthcare utilization [29,60,61]. Mothers who have adequate antenatal care visits receive information and sensitization about preparedness and expectations during labor [62].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the associated factors to this suboptimal care include the lack of knowledge and skills to recognize and address emerging intrapartum complications [26,27], negative attitudes towards care among health care providers, low sta ng levels and demotivation among health care providers, and poor adherence to patient management guidelines [28]. Socio-demographic factors associated with quality of intrapartum care include planned status of pregnancy, number of antenatal visits attended, duration of labor, presence of quality services by region, advanced maternal age, education level and employment status [29][30][31]. Other factors include the type of facility, availability of routine supplies, distance to facility, in-service training, and supervision of health care providers [12,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal satisfaction among women who gave birth in African nations was 78.54%, 94%, and 92.54% in Egypt, Ghana,and Mozambique respectively (10)(11)(12). However, in Ethiopia, the magnitude of moms who were happy with child bearing care ranged from 19% to 87.2% (13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal satisfaction among women who gave birth in African nations was 78.54%, 94%, and 92.54% in Egypt, Ghana, and Mozambique, respectively ( 13 15 ). However, in Ethiopia, the proportion of women who were satisfied with child bearing care ranged from 19% to 87.2% ( 16 21 ).…”
Section: Introductionmentioning
confidence: 99%